In-flight validation of rotorcraft emission predictions and low-pollutant mission - Frassoldati, A.; Cuoci, A.; Faravelli, T.; Ferrante, A.; Stachurska, M.; Redaelli, M.; Riviello, L. (My University, 2015)
This paper deals with the development of a predictive tool to estimate the Rolls-Royce Allison 250-C20B engine emissions, when installed on the PZL SW-4 helicopter. To confirm the prediction capability achieved, an ad-hoc methodology has also been developed for the in-flight measurement of emissions. The results have been critically analysed, with the aim of producing guidelines for low-pollutant light single-engined helicopter missions.
Keywords: Green Rotorcraft